2021
DOI: 10.3390/ijerph18052327
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Behavioral Intentions towards Low-Carbon Travel: Extending the Theory of Planned Behavior

Abstract: With the rapid development of China’s economy and the rapid growth of the population, the demand for traffic is gradually changing from slow to fast, and the traffic congestion, air pollution, climate change and public health problems are becoming increasingly prominent. As residents’ willingness for low-carbon travel plays a crucial role in alleviating the problems caused by traffic, many studies pay attention to this aspect, but young people are still an obviously neglected group in the study of willingness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 69 publications
4
23
1
Order By: Relevance
“… Boguszewicz-Kreft et al (2020) have verified the TPB model’s applicability to medical tourism and compared the differential willingness among consumers of different nationalities to use medical tourism services. Hu et al (2021) have found that attitudes, perceived behavioral control, environmental awareness, and perceived moral obligations are significantly and positively correlated with young people’s intent for low-carbon travel behavior, while subjective norms are not. Chen et al (2019) have applied TPB to a study of pro-environmental tourism behavior among urban residents, finding that intentions and habits are the key influential factors, while attitudes have the most significant impact on behavioral intention.…”
Section: Theoretical Background and Hypothetical Developmentmentioning
confidence: 98%
“… Boguszewicz-Kreft et al (2020) have verified the TPB model’s applicability to medical tourism and compared the differential willingness among consumers of different nationalities to use medical tourism services. Hu et al (2021) have found that attitudes, perceived behavioral control, environmental awareness, and perceived moral obligations are significantly and positively correlated with young people’s intent for low-carbon travel behavior, while subjective norms are not. Chen et al (2019) have applied TPB to a study of pro-environmental tourism behavior among urban residents, finding that intentions and habits are the key influential factors, while attitudes have the most significant impact on behavioral intention.…”
Section: Theoretical Background and Hypothetical Developmentmentioning
confidence: 98%
“…Behavioral intention is the most important factor between an individual’s inner thoughts and actual actions and refers to the willingness of a person to perform a given behavior [ 15 , 43 ]. Hu, Wu and Chen [ 15 ] and Kuo and Dai [ 31 ] pointed out that the most important factor in determining an individual’s behavior is his or her intention to engage in the act. This view was confirmed by Shin and Kang [ 44 ] to protect environmental behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consumers’ green commitments to the environment is considered an important factor for predicting environmentally responsible behavior in traveling (Safari, Salehzadeh, Panahi and Abolghasemian [ 10 ]). Although some studies have been conducted in the field of tourists’ low-carbon travel behavior [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], additional empirical evidence is needed to be gathered before we can be sure of the causal impacts of the results. Especially, there is a need to focus on the mechanisms through which various personal and contextual antecedents influence tourists’ low-carbon travel behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Eagly and Chaiken [ 46 ], attitude was explained as a function of individuals’ behavioral beliefs (BB) which reflect the perceived consequences or outcomes of the behavior and their assessment of the outcome evaluation (OE). That is, people generally evaluate the benefits and costs during their decision-making process whether to conduct a specific behavior or not [ 47 ]. Either a favorable or unfavorable attitude depends on their evaluation of consequences [ 20 , 26 , 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hwang, Kim, et al [ 26 ] employed Ajzen’s TPB framework to comprehend individuals’ intention formation in the foodservice innovation, and their analysis results using 406 samples displayed the strong association between perceived behavioral control and behavioral intentions. Hu et al [ 47 ] studied younger generations’ decision making process in the tourism context, and their findings indicated that the perception of young people about their high ability of control over their behavior exerted a significant influence on their pro-environmental travel choice. Accordingly, it is anticipated that when individuals have confidence and proper resources in visiting restaurants offering foods made by edible insects, there are high possibilities that these individuals will visit an edible insect restaurant.…”
Section: Literature Reviewmentioning
confidence: 99%